Aproximación al estudio sobre el Modelo de mujer espiritual de los eclesiásticos en la Edad Moderna. - FUSTER, FRANCISCO PONS (Scripta, 2016)
The model of a spiritual woman, a laywoman (beata), was always the same all throughout Modern Age. In all women's lives, biographers followed a pattern or archetype and this was reproduced until well into the eighteenth century, and persisted up to the ninteenth century. However, it is necessary to explore each biography in more detail, to understand that each woman's life was also one and unique. Only in that way, each of those women will be able to recover the prominence they once had.